2018
DOI: 10.3389/fimmu.2018.02165
|View full text |Cite
|
Sign up to set email alerts
|

Notch and NF-κB: Coach and Players of Regulatory T-Cell Response in Cancer

Abstract: The Notch signaling pathway plays multiple roles in driving T-cell fate decisions, proliferation, and aberrant growth. NF-κB is a cell-context key player interconnected with Notch signaling either in physiological or in pathological conditions. This review focuses on how the multilayered crosstalk between different Notches and NF-κB subunits may converge on Foxp3 gene regulation and orchestrate CD4+ regulatory T (Treg) cell function, particularly in a tumor microenvironment. Notably, Treg cells may play a pivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 112 publications
1
49
0
Order By: Relevance
“…Also, others have reported that nonlymphoid tissue Tregs display an activated phenotype compared with lymphoid organ and circulating Tregs ( 12 , 20 , 73 ). Both BATF and the TNFRSF/NF-κB signaling axis are crucial in the survival of Tregs and maintenance of a stable effector Treg phenotype, especially in tissues ( 15 , 28 , 32 , 33 , 78 , 79 , 101 ). It is now recognized that Tregs adapt to their tissue environments, with, on the one hand, common adaptations across many tissues — such as increased expression of IL10, IL1RL1 (encoding ST2, an IL-33 receptor subunit), AREG (encoding amphiregulin), CTLA4, TIGIT, BATF, and IRF4 and decreased expression of LEF1, TCF7 — but, on the other hand, importantly, tissue-specific signatures ( 12 , 13 , 15 , 16 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, others have reported that nonlymphoid tissue Tregs display an activated phenotype compared with lymphoid organ and circulating Tregs ( 12 , 20 , 73 ). Both BATF and the TNFRSF/NF-κB signaling axis are crucial in the survival of Tregs and maintenance of a stable effector Treg phenotype, especially in tissues ( 15 , 28 , 32 , 33 , 78 , 79 , 101 ). It is now recognized that Tregs adapt to their tissue environments, with, on the one hand, common adaptations across many tissues — such as increased expression of IL10, IL1RL1 (encoding ST2, an IL-33 receptor subunit), AREG (encoding amphiregulin), CTLA4, TIGIT, BATF, and IRF4 and decreased expression of LEF1, TCF7 — but, on the other hand, importantly, tissue-specific signatures ( 12 , 13 , 15 , 16 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both hyperactive Notch1 and Notch3 enhances CXCR4 expression in thymus-derived and in BM-derived T-cells in T-ALL [106,107], and CXCR4 silencing inhibited the expansion of leukemic cells [106] through disruption of the Notch/CXCR4 partnership [102]. Of note, NFκB enhanced generation of Treg, suppressing the antitumor immune response in a Notch3-dependent T-ALL mouse model [108]. In AML, the activation of CXCR4 is critical for the migration and retention of leukemia cells within the BM, for extramedullary metastasis, chemotherapy resistance [109], and for the maintenance of minimal residual disease (MRD) [110].…”
Section: Cxcl12/cxcr4 Axis In Hematological Tumors: a Crucial Hub Formentioning
confidence: 98%
“…Also others have found that non-lymphoid-tissue Tregs display an activated phenotype compared to lymphoid-organ and circulating Tregs, 13,18,80 and both BATF and the TNFRSF-NF-κB signaling axis have been described as crucial in the survival of Tregs and maintenance of a stable effector Treg phenotype, especially in tissues. 16,28,32,33,85,86,108 It is now recognized that Tregs adapt to their tissue environments, with common adaptations across many tissues, such as increased expression of IL10, IL1RL1 (encoding ST2, an IL-33 receptor subunit), AREG (encoding amphiregulin), CTLA4, TIGIT, BATF and IRF4, and a low expression of LEF1 and TCF7 compared to lymphoid tissue Tregs, but, importantly, also tissue-specific signatures. 12,13,16,17,21 These tissue-specific transcriptomic profiles counter the notion that tissue Tregs merely have a more activated, effector or memory state than lymphoid-organ Tregs.…”
Section: Discussionmentioning
confidence: 99%